Making Charcoal Water Electrodes - Amalia Amira Rashidah; Amar Lohot Tanjung; Sindi H Sembiring (Indonesian Journal of Chemical Science and Technology (IJCST), 2021)
Charcoal is the residual waste from the heat decomposition process of carbon-containing materials, most of whose components are carbon. This study aims to determine the frequency of charcoal water as an electrolyte solution to produce an alternative energy source that is environmentally friendly. The method used in the experiment is to find the type of water with the addition of zinc and copper and to measure the sample voltage of charcoal water to determine the optimum mass and optimum interaction time. The variation in the volume of water with 50 ml and 100 ml of charcoal water was produced, with the addition of zinc and copper in the size of 1x5 cm, 2x5 cm, 3x5 cm which resulted in fluctuations in each data. For example, the difference in voltage value in the type of water used is tap water, 100 ml well water with the addition of zinc and copper measuring 2x5 cm. Tap water, namely with an electric voltage of 0.65 V, 0.70 V, 0.60 V, 0.60 V, 0.75 V and well water with an electric voltage of 0.60 V, 0.55 V, 0.55 V, 0.55 V, 0.55 V. Less than the maximum frequency produced with two glasses that are not made into a series or parallel circuit.